Cerebrospinal Fluid Biomarkers of Alzheimer's Disease Show Different but Partially Overlapping Profile Compared to Vascular Dementia - Llorens, Franc; Schmitz, Matthias; Knipper, Tobias; Schmidt, Christian; Lange, Peter; Fischer, Andre; Hermann, Peter; Zerr, Inga (Frontiers in Aging Neuroscience, 2017)
Vascular factors increase the risks of developing Alzheimer’s disease (AD) and they contribute to AD pathology. Since amyloid beta (Ab) deposits can be observed in both diseases, there is an overlap which impedes a clear discrimination and difficult clinical diagnosis. In the present study, we compared cerebrospinal fluid (CSF) profiles of neurodegenerative and inflammatory biomarkers in a patient cohort of controls (n=50), AD (n=65) and vascular dementia (VaD) (n=31) cases. Main results were validated in a second cohort composed of AD (n=26), rapidly progressive AD (rpAD) (n=15), VaD (n=21) and cognitively unimpaired patients with vascular encephalopathy (VE) (n=25) cases. In the study cohort significant differences were detected in tau, p-tau and Ab1-42 (Ab42) levels between AD and VaD patients, but not for the neuron-specific enolase (NSE), S100B protein, 14-3-3 and YKL-40. Differential tau, p-tau and Ab42 levels between AD and VaD were confirmed in the validation cohort, which additionally showed no differences between AD and rpAD, nor between VaD and VE. The evaluation of the biomarker accuracy in discrimination between AD and VaD patients revealed that the best diagnostic accuracy could be obtained when tau, p-tau and Ab42 were combined in form of Ab42/p-tau (AUC 0.84- 0.90, sensitivity 77-81%, specificity 80-93%) and (tau x p-tau)/Ab42 ratio (AUC 0.83-0.87, sensitivity 73-81%, specificity 78-87%). Altogether, our studies provided neurodegenerative biomarker profiles in two cohorts of AD and VaD patients favoring the combination of CSF biomarker to differentiate between diseases.